Establishing the kinematics of the North East Region of South Africa with the use of GPS data - Desai, Ahmad (School of Architecture, Planning and Geomatics, 2016)
The Nubia-Somalia boundary is one of the least well defined plate boundaries. The southern extension, as it extends through the latitudes that are co-incidental to South Africa's geographical extent has not been defined. This project analyses Trignet data, supplemented with other available Nubian GPS data, to determine whether the North East Region of South Africa is segregated from the Nubian Plate. A ten year GPS time series (processed using the Bernese 5.0 precise GNSS software) is minimally constrained to the ITRF2008, using the reprocessed IGS08 products. This processed data was managed to alleviate GPS time series bias, which includes seasonal effects, the determination of GPS velocity uncertainty using a white+ icker noise model, discontinuity detection using Roggero's (2012) discontinuity algorithm and an outlier detection using an algorithm developed for this project for each of the 104 stations incorporated in the network. The computed velocities were compared to the ITRF2008 published velocities and a RMS of the post t residuals of 0.4, 0.4 and 0.7 mm/yr for the North, East and Height were computed respectively. This RMS is of similar magnitude to the WRMS of the post t velocity residuals in computing transformation parameters from ITRF2005 to ITRF2008, suggesting that the threshold of ITRF2008 velocity precision has been obtained. The resultant Euler vector was scrutinised on three fronts: an Euler vector rep- resenting the geographical extent of South Africa, an Euler vector in which the height velocity was minimised to zero and an Euler vector representing the North East Region of South Africa. All computed Euler vectors are consistent, suggesting a uniform South African GPS velocity field. The Euler vector representative of South Africa's uniform velocity field has an angular velocity of 0.273 deg/Myr, with a pole of rotation at lat 50.85 and long -82.83 degrees and is consistent with the Euler vectors computed by Altamimi et al. (2012) and Malservisi et al. (2013) for Africa and South Africa respectively. The consistency of the Euler vector suggests that South Africa is underlain by a single plate (i.e. the Nubian Plate), and that the East African Rift valley does not extend into South Africa. Hence, for future tectonic studies and long term reference frame solutions, stations such as HARB, HRAO and RBAY should be included, as they are not located in deformation zones.